Hattat Musikişinas Hacı Nuri Korman`ı Anma Toplantısı - İhsanoğlu, Ekmeleddin, 1943-; Derman, Mustafa Uğur, 1935- (My University, 1986)
Hattat Musikişinas Hacı Nuri Korman'ın hayatı ve çalışmaları, eserleri hakkında bilgi verilmektedir.
WAV and MP3 formats were created from the original audio cassettes along with the CD.
There is humming and intermittent gaps in the recording.
Keywords: Conferences; Korman, Nuri, 1868-1951.